THE RELATIVE IMPORTANCE OF INVENTORY IN THE FINANCIAL STATEMENTS IN TERMS OF FINANCIAL RATIOS AND ITS IMPACT ON EVALUATING THE EFFICIENCY OF PERFORMANCE BY APPLICATION IN THE GENERAL COMPANY FOR TEXTILE AND LEATHER INDUSTRIES (World Economics and Finance Bulletin, 2024)
The research focused on the relative importance of inventory in the financial statements in terms of financial ratios and its impact on evaluating performance efficiency and highlighting introductory entries on the importance of inventory and analyzing its value in the financial statements using financial ratios and comparisons. This was applied in the research sample, the General Company for Textile and Leather Industries, and the trading ratio and the activity ratio in the researched company were used. It reached a set of conclusions, the most important of which is the decline in the quick liquidity ratio, which reached in the year2020 (0.247) to (0.193) in the year 2021. This is a negative indicator that is reflected in the company’s performance. As for the recommendations, the most important of them is the need for economic units to rely on modern financial indicators when evaluating financial decisions related to economic units.
Keywords: financial statements; financial ratios; inventory; efficiency of performance